In silico analysis of the potential mechanism of a preventive Chinese medicine formula on coronavirus disease 2019. (15th July 2021) - Wu, Huaying; Gong, Ke; Qin, You; Yuan, Zhiying; Xia, Shuaishuai; Zhang, Shiying; Yang, Jingjing; Yang, Ping; Li, Liang; Xie, Mengzhou
Abstract: Ethnopharmacological relevance: With the spread of Coronavirus Disease (2019) (COVID-19), combination with traditional Chinese medicine (TCM) has been widely used as a prevention and therapy strategy in China. Xin guan No.1 (XG-1) prescription is a preventive formula recommended by the Hunan Provincial Administration of TCM to prevent the pandemic of COVID-19. Aim of the study: To explore the potential preventive mechanisms of XG-1 against COVID-19 in the combination of network pharmacology approach, single-cell RNA expression profiling analysis, molecular docking and retrospective study. Materials and methods: Encyclopedia of Traditional Chinese Medicine (ETCM) database was used to determine the meridian tropism, active components and target genes of XG-1. Gene ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analysis were conducted by R Cluster Profiler package (3.14.3). Single cell RNA sequencing (scRNA-seq) data of human lung (GSE122960) was downloaded from Gene Expression Omnibus (GEO) database and analyzed by R Seurat package (3.1.2). Cytoscape (3.7.2) was used to construct the interaction network. The main ingredients in XG-1 were identified by HPLC- Q-TOF- MS and used for molecular docking with COVID-19 3CL hydrolytic enzyme and angiotensin converting enzyme II (ACE2). A retrospective study of 47 close contact participants from Dongtang Community of Hunan Province was conducted to evaluated the preventive effect of XG-1. Results: According to the network pharmacology analysis, XG-1 formula was closely related to lung-, spleen- and stomach-meridians and include a total of 206 active components and 853 target genes. GO and KEGG pathway enrichment revealed that XG-1 mainly regulated cellular amino acid metabolism process and neuroactive ligand-receptors interaction. The scRNA-seq profiling showed that angiotensin converting enzyme 2 (ACE2) was principally expressed in alveolar type 2 epithelial cells (AT2). 153 genes were up-regulated in AT2 cells expressing ACE2 and 12 genes were obtained by intersecting with XG-1 target genes, of which 3 were related to immunity. Five main chemical ingredients were detected in XG-1 sample by HPLC-Q-TOF-MS. The molecular docking showed that Rutin, Liquiritin and Astragaloside Ⅳ had a good affinity with COVID-19 3CL hydrolytic enzyme and ACE2. Compared with participants who didn't take XG-1, preventive treatment with XG-1gradules resulted in a significant lower rate of testing positive for SARS-CoV-2 nucleic acid (P < 0.0001). Conclusion: The present study showed that XG-1 exerts a preventive effect in close contacts against COVID-19. The underlying mechanism may be related to modulate immunity response through multiple components, pathways, and several target genes co-expressed with ACE2. These findings provide preliminary evidences and methodological reference for the potential preventive mechanism of XG-1 against COVID-19. Graphical abstract: Image 1